Commercial Applications of Blockchain and Distributed Ledger Technology - Gutlapalli, Sai Srujan (Engineering International, 2016)
Blockchains are distributed ledgers. Distributed ledgers replace centralized ledgers. Distributed ledgers use nodes—computers—to record, share, and synchronize transactions in their electronic ledgers. The paper examines how blockchain data is arranged into blocks and how an append-only mode chain links them. Distributed ledger technology (DLT) encrypts and consensuses immutable and sequential transaction records. Bitcoin pioneered blockchain. Since then, many blockchains with decentralization, encryption, consensus, and immutability have been developed for diverse uses. Blockchain technology is most typically used in transaction settlement, digital currency banks, and supply chain applications to solve problems quickly. The study examines how blockchain and DLTs might improve information management and build new technologies like the Internet of Things. The study shows how legal issues encourage blockchain technology despite limited international and federal restrictions. However, data privacy and security must be addressed immediately.
Keywords: Blockchain; Commercial Applications; Distributed Ledger Technology